2022
DOI: 10.1111/jam.15619
|View full text |Cite
|
Sign up to set email alerts
|

Dual species dry surface biofilms; Bacillus species impact on Staphylococcus aureus survival and surface disinfection

Abstract: Aims: Dry surface biofilms (DSB) survive on environmental surfaces throughout hospitals, able to resist cleaning and disinfection interventions. This study aimed to produce a dual species DSB and explore the ability of commercially available wipe products to eliminate pathogens within a dual species DSB and prevent their transfer. Methods and Results:Staphylococcus aureus was grown with two different species of Bacillus on stainless steel discs, over 12 days using sequential hydration and dehydration phases. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
(81 reference statements)
1
7
0
2
Order By: Relevance
“…Viable bacteria recovered from unwiped coupons pretreated with formulations A, D, E, and F were not significantly different to water treated coupons. This data corroborates results from other studies on different bacteria where mechanical removal was shown to be essential to appropriately reduce DSB on surfaces (Centeleghe et al, 2022; Ledwoch, Magoga, et al, 2021). Our findings support evidence that a “clean” food surface should be generated by the combined approach of mechanical removal and effective biocide use (Gibson et al, 1999).…”
Section: Resultssupporting
confidence: 91%
“…Viable bacteria recovered from unwiped coupons pretreated with formulations A, D, E, and F were not significantly different to water treated coupons. This data corroborates results from other studies on different bacteria where mechanical removal was shown to be essential to appropriately reduce DSB on surfaces (Centeleghe et al, 2022; Ledwoch, Magoga, et al, 2021). Our findings support evidence that a “clean” food surface should be generated by the combined approach of mechanical removal and effective biocide use (Gibson et al, 1999).…”
Section: Resultssupporting
confidence: 91%
“…On the one hand, in vitro and in vivo models based on monospecies cultures and biofilms have been established for decades and provide an abundance of important data. On the other hand, there are several lines of evidence of interference due to (a) different active compounds being administered simultaneously [ 33 , 34 ]; (b) the effects of microbes on each other [ 19 , 35 , 36 ]; (c) modulation of an active compound effect on the first microbe in the presence of a second microbe in a dual-species community [ 37 , 38 , 39 ]. Hence, the presence of a counterpart in the simplest dual community may significantly change the effect of a hormone or any other active compound on a microbe.…”
Section: Discussionmentioning
confidence: 99%
“…DSB in the food industry represents an emerging and promising research field. Few studies have observed biofilm formation on dry surfaces in the food industry (Harada & Nascimento, 2021a, 2021b; Iibuchi et al., 2010), as well as evaluated the responses to sanitation in the hydration and desiccation cycles, as has been done for healthcare surfaces (Centeleghe et al., 2022; Ledwoch & Maillard, 2019).…”
Section: Dsbs In the Food Industrymentioning
confidence: 99%